Can we Predict Inflation in Tunisia? An Analysis Following an Unobserved Components Model (Global Journal of Management and Business Research, 2015)
Empirical analysis on the prediction of inflation is becoming more and focus on advanced economies. At least three factors explain this. First, the predominance of agriculture in developing countries makes it dependent inflation climatic conditions of economic activity (eg, Phillips curve). Then, the limits on the quality and frequency data are often limiting factors. Finally, emerging markets are likely to suffer sudden crises and reversals of macroeconomics variables and it is therefore difficult to identify an economic regularity. However, a growing body of research has begun to analyze the inflation forecasts in emerging and developing leading indicators for inflation.
Keywords: forecasting inflation; phillips curve; economic regularity; underlying inflation